Zinc oxide nanoparticles impair bacterial clearance by macrophages. (July 2014) - Lin, Chia-Der; Kou, Yu-Yi; Liao, Chin-Yu; Li, Ching-Hao; Huang, Shiao-Ping; Cheng, Yu-Wen; Liao, Wei-Chih; Chen, Hao-Xiang; Wu, Pei-Ling; Kang, Jaw-Jou; Lee, Chen-Chen; Lai, Chih-Ho
Aim: The extensive development of nanoparticles (NPs) and their widespread employment in daily life have led to an increase in environmental concentrations of substances that may pose a biohazard to humans. The aim of this work was to examine the effects of zinc oxide nanoparticles (ZnO-NPs) on the host's pulmonary immune system response to nontypeable Haemophilus influenzae (NTHi) infection.Materials & Methods: A murine infection model was employed to assess pulmonary inflammation and bacterial clearance in response to exposure to ZnO-NPs. The molecular mechanisms underlying ZnO-NP-impaired macrophage activation were investigated.Results: Treatment with ZnO-NPs impaired macrophage activation, leading to a delay in NTHi clearance in the bronchial alveolar lavage fluids and lungs. Exposure to ZnO-NPs followed by NTHi challenge decreased levels of nitric oxide compared with NTHi infection alone. The effects of ZnO-NPs involved downregulation of NTHi-activated expression of inducible nitric oxide synthase and the translocation of active NF-kB into the nucleus.Conclusion: These results demonstrate that exposure to ZnO-NPs can impair innate immune responses and attenuate macrophage responses to bacterial infection. Original submitted 17 December 2013; Revised submitted 3 March 2014